2014
DOI: 10.3727/154427314x14056884441905
|View full text |Cite
|
Sign up to set email alerts
|

Learn While Cruising: Experiential Learning Opportunities for Teaching Cruise Tourism Courses

Abstract: This article follows up on the seminal experience written by Weeden, Woolley, and Lester in 2011 where a cruise field trip was undertaken with a group of undergraduate students in the UK. It presents the reflections of students who undertook a cruise field trip carried out in Australia with 24 undergraduate students. While some of the experiential learning findings obtained in this research (n = 22) support what was presented from the smaller sample of the above-mentioned article (n = 8)—facilitation of group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Other factors that could influence students' learning outcomes are the structure of the fieldwork, setting novelty, prior knowledge and interest of the students, the social context of the visit, instructor agendas, student experiences during the field trips and the presence or absence and quality of preparation and follow up (De Witt & Storksdieck, 2008). Lohmann (2014) found that, by taking students on a cruise, instructors of tourism courses accomplished several educational goals, such as: immerse students in an authentic tourism and hospitality experience, provide them with an opportunity to interact with professionals and to learn by observing them, allow them to observe how marketing is done, and instil a sense of community and building relationships. Hovorka and Wolf (2009) wanted to evaluate the quality of learning experiences as perceived by 28 students who participated in a residential field course.…”
Section: Fieldwork In Tourismmentioning
confidence: 99%
“…Other factors that could influence students' learning outcomes are the structure of the fieldwork, setting novelty, prior knowledge and interest of the students, the social context of the visit, instructor agendas, student experiences during the field trips and the presence or absence and quality of preparation and follow up (De Witt & Storksdieck, 2008). Lohmann (2014) found that, by taking students on a cruise, instructors of tourism courses accomplished several educational goals, such as: immerse students in an authentic tourism and hospitality experience, provide them with an opportunity to interact with professionals and to learn by observing them, allow them to observe how marketing is done, and instil a sense of community and building relationships. Hovorka and Wolf (2009) wanted to evaluate the quality of learning experiences as perceived by 28 students who participated in a residential field course.…”
Section: Fieldwork In Tourismmentioning
confidence: 99%